HUBUNGAN LINGKUNGAN KERJA DENGAN PRODUKTIVITAS KERJA KARYAWAN SALON KECANTIKAN DI KOTA PEKANBARU - Putri, Mia Leveria (RC-INSTITUT, 2019)
The background of this research is knowing the relationship between working environment to the work productivity of salon employees in the handsome district of Pekanbaru. This research aims to analyse physical work environment, non physical working environment and working environment relationship (physical and non-phic) with employee productivity at Beauty Salon at handsome Pekanbaru Sub-district. Current research is a descriptive type of associative. The population in this study is a customer of a beauty salon with sampling techniques using accidental. Data types use primary data and secondary data. Variables in this study use work productivity, physical work environments and non-physical work environments. Data collection techniques are performed by observation and questionnaire. Test the data instrument in this study is the validity test and reliability test. Data analysis using methods of quantitative analysis techniques and hypothesized stages of testing are performed using statistical test tools. The results showed that the first hypothesized test results were seen that the resulting T-count value was 0116 that value was strengthened by a sig of 0.007. The data processing process is done using error rate of 0.05. Results obtained showing a sig value of 0.007 is below the error rate of 0.05 it can be concluded that the physical work environment is positively and significantly related to the work productivity of the beauty salon employees in the city Pekanbaru. The results of the second hypothesis test by using a non-physical working environment variable that has been done is seen that the resulting T-count value is 0258 that value is strengthened by the sig by 0.000. The data processing process is done using error rate of 0.05. Results obtained showing a sig value of 0.000 is below the error rate of 0.05 then it can be concluded that the non-physical work environment is positively and significantly related to the work productivity of the beauty salon employees in the city Pekanbaru.